2014
DOI: 10.1097/crd.0b013e31829cf733
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Diastolic Dysfunction

Abstract: Left ventricular diastolic dysfunction (DD) is recognized as an important contributor to diastolic heart failure and is associated with increased morbidity and mortality. The evaluation of diastolic function has become an integral part of a full echocardiographic study and is recommended by the current guidelines of the American Society of Echocardiography and the European Association of Cardiovascular Imaging. Recent data show that diastolic function is not static, but rather a dynamic phenomenon; worsening o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 110 publications
1
29
0
3
Order By: Relevance
“…Based upon current literature, diastolic dysfunction appears to represent an early marker of subclinical cardiovascular disease [5, 15]. There is increasing evidence demonstrating the independent predictive value of diastolic dysfunction [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based upon current literature, diastolic dysfunction appears to represent an early marker of subclinical cardiovascular disease [5, 15]. There is increasing evidence demonstrating the independent predictive value of diastolic dysfunction [15].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence demonstrating the independent predictive value of diastolic dysfunction [15]. Further studies should replicate this in other minority populations and then prospectively study whether any of these risk factors can be modified and if so does that slow the progression of diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have estimated the prevalence of subclinical diastolic dysfunction can be as high as 48% among high-risk groups with cardiovascular risk factors. 7,8 Levy et al in a cohort of African American patients identified from an urban ED found a 90% point prevalence of subclinical hypertensive heart disease. 9 Left ventricular hypertrophy (LVH) is one of the strongest predictors of adverse cardiovascular outcomes in a hypertension population.…”
Section: Introductionmentioning
confidence: 99%
“…Left ventricular diastolic dysfunction (LVDD) is recognized as an important contributor to diastolic heart failure and is associated with increased morbidity and mortality (1). Hypertension and cardiac ischemia are the most common causes of diastolic heart failure (2).…”
Section: Introductionmentioning
confidence: 99%